2023
DOI: 10.1177/0961463x231187702
|View full text |Cite
|
Sign up to set email alerts
|

Teaching complex time through pattern thinking and understanding

Abstract: To move beyond its industrial era mechanistic paradigm, western education needs to include knowledges that enable students to think with and engage an increasingly complex world. The teaching and learning of complex time is one such knowledge, and pattern thinking and understanding are useful for this undertaking. As part of their teaching practice, the author developed and implemented a patterns-based design and educational strategy called spiraltime patterning with secondary school students more than a decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…After observing and talking with the students, it was concluded that the mechanistic temporal and organisational linearities of educational process were dampening their consciousness, their engagement with life all around them, and compromising their learning. Linear reductive temporal practices specifically were contributing to disengagement through a reductive and dissociative effect on the students' conscious presence (Brown, 2023). Mechanistic linear time within education standardises and commodifies all learning, resulting in alienation and disassociation from subjective temporalities and therefore the experience of existence for students (Alhadeff-Jones, 2017).…”
Section: Emergence Of Complexity Patterningmentioning
confidence: 99%
“…After observing and talking with the students, it was concluded that the mechanistic temporal and organisational linearities of educational process were dampening their consciousness, their engagement with life all around them, and compromising their learning. Linear reductive temporal practices specifically were contributing to disengagement through a reductive and dissociative effect on the students' conscious presence (Brown, 2023). Mechanistic linear time within education standardises and commodifies all learning, resulting in alienation and disassociation from subjective temporalities and therefore the experience of existence for students (Alhadeff-Jones, 2017).…”
Section: Emergence Of Complexity Patterningmentioning
confidence: 99%